Supercomputer Simulations of Nondestructive Tomographic Imaging with Rotating Transducers - Romanov, Sergey Y. (Supercomputing Frontiers and Innovations, 2018)
A method of nondestructive ultrasound tomographic imaging employing a rotating transducer system is proposed. The rotating transducer system increases the number of emitters and detectors in a tomographic scheme by several times and makes it possible to neutralize image artifacts resulting from incomplete-data tomography. The inverse problem of tomographic reconstructing the velocity structure inside the inspected object is considered as a nonlinear coefficient inverse problem for a scalar wave equation. Scalable iterative algorithms for reconstructing the longitudinal wave velocity inside the object are discussed. The methods are based on the explicit representation for the gradient of the residual functional. The algorithms employ parallelizing the computations over emitter positions. Numerical simulations performed on the “Lomonosov-2” supercomputer showed that the tomographic methods developed can not only detect boundaries of defects, but also determine the wave velocity distribution inside the defects with high accuracy provided that both reflected and transmitted waves are registered.